STUDI EFISIENSI PENGOLAHAN LIMBAH CAIR INDUSTRI BANTALAN UNTUK DIGUNAKAN KEMBALI OLEH MENARA PENDINGIN - Triparma Gurning, Chrisnathan
ABSTRACT. Water is a basic need for the survival of living things, one of which is in the form of industrial activities. The Province of DKI Jakarta has a high population and activity level with 2374 Manufacturing Industry companies based on BPS 2019. With that, the United Nations declared Sustainable Development Goals (SDGs) with one of the points in the form of Industry, Innovation and Infrastructure which explains the discovery and application of innovations for sustainable industrial activities. PT X, which is a bearing manufacturing industry located in the Cakung sub-district, consumes 1,101.6 m3 /month for cooling tower makeup water, and 766.5 m3 /month for domestic and industrial activities as where all of the waste water that is generated, is treated and reused for the cooling tower makeup water. This research was made by examining the waste water treatment plant with the means of applying efficient reuse of waste water from an environmental and economic perspective. To understand the WWTP used by PT X, measurements of parameters were carried out at six (6) points with parameters such as pH, Temperature, TDS, Alkalinity, Hardness, BOD, and COD where based on research, industrial effluent wastewater has a pH of 5, 4 with a temperature of 33.5oC, a TDS of 2500 mg/L, a BOD of 3282.2 mg/L O2, a COD of 8153 mg/L O2, a total hardness of 351 mg/L, and a total alkalinity of 52 mg/L CaCO3. Liquid waste generated from PT X office activities is blackwater which has a pH value of 6.4 with a temperature of 31.5oC, a TDS of 483 mg/L, a BOD of 2124 mg/L O2, a COD of 4659.2 mg/L O2, a total hardness of 252 ,15 mg/L, and a total alkalinity of 8 mg/L CaCO3. These parameters are used to determine the Cycle of Concentration (COC) value allowing the ability to calculate the water lost by evaporation, driftloss, and blowdown hence obtaining the makeup water needs. Also, these parameters are used to calculate LSI and RSI to determine the possibility of scaling, fouling and corrosion in cooling towers. It was found that using permeate Reverse Osmosis increased the COC value up to 44 so that it could reduce the need for makeup water by 31% and reduce cooling tower blowdown by 91%, but has tendencies of corrosion. The costs of installation and the pre-treatment is valued at Rp. 415.153.402.61 with the operating costs of Rp. 298.131.000.12 with a NPV value that is greater than not reusing wastewater nor using the existing methods of water conservation.